Identification and prioritization of coordination barriers in humanitarian supply chain management - Kabra, G.; Ramesh, A.; Kaur, Arshinder (Elsevier BV, 2015)
In the wake of disaster, several organizations work for the welfare of the disaster victims, although lack of coordination among them hampers the performance of relief operations. This study sets out to explore and prioritize the coordination barriers in the humanitarian supply chain management (HSCM), particularly in the Indian context to enhance the performance of relief operations. The study is divided into three phases. Initially, barriers to coordination were identified through an extensive literature review, allied to brainstorming sessions with experts. These were then grouped into 5 categories, i.e. management barriers, technological barriers, cultural barriers, people barriers and organizational barriers. Secondly, a survey questionnaire was designed, tested and refined to incorporate the views of the managers involved in the relief operations of the disaster that occurred in the Uttarakhand (a Northern state in India) on June 14, 2013 in order to empirically verify the barriers to coordination. Finally, barriers were prioritized on the basis of their severity using fuzzy analytic hierarchy process (F-AHP) which considers the uncertainty of the data and impreciseness rather than crisp value. The results indicate that lack of top management commitment, improper organizational structure to create and share knowledge and lack of policy for coordination are the major barriers. These are the areas that need to be handled first in order to remove coordination barriers. The findings of the study throw some new light on the coordination issues in HSCM and provide a more effective, efficient, robust and systematic way to overcome coordination barriers.